The Expression and Prognostic Value of FGF2, FGFR3, and FGFBP1 in Esophageal Squamous Cell Carcinoma - Wenjing Zhang; Yaxing Zhou; Chao Li; Shanshan Xu; Mengyan Li; Wenying Liu; Yuqing Ma; Hui Wang (Analytical Cellular Pathology)
Background. Esophageal squamous cell carcinoma was treated by operation and chemoradiotherapy. However, the prognosis of most patients is poor after treatment, and most studies have shown that FGF2 and its receptor (FGFR) are involved in the development of various malignant tumors. FGF2 plays an important role in tumor progression and malignancy. In this study, the immunohistochemistry of FGF2, FGFR3, and FGFBP1 was used to further verify the expression of the three proteins in 172 patients with esophageal squamous cell carcinoma (ESCC) who had not received preoperative chemoradiotherapy and its effect on the prognosis of ESCC. Methods. (1) χ2 test was used to analyze the relationship between proteins and clinicopathological parameters. Survival analysis was used to investigate the effect of three proteins on prognosis. (2) Paired sample t-test was used to analyze the mRNA expression of the three proteins in fresh ESCC tissues and adjacent normal tissues. Results. FGF2 was correlated with tumor size (p=0.026), gender (p=0.047), and lymph metastasis (p=0.007) in ESCC tissues. The high expression of FGFR3 was associated with tumor differentiation (p=0.043 and p<0.05), lymph node metastasis (p=0.078 and p<0.1), and race (p=0.033 and p<0.05). The high expression of FGFBP1 was significantly associated with the degree of tumor differentiation (p=0.012), age (p=0.045), and lymph node metastasis (p=0.032) of ESCC patients. The expression of FGF2, FGFR3, and FGFBP1-mRNA in ESCC tissues was significantly higher than that in adjacent tissues (p<0.001, p<0.001, and p=0.001). Patients with high expression of FGF2, FGFBP1, and FGFR3 had poor prognosis. There was a weak positive correlation between FGF2 and FGFBP1, as well as FGFR. Conclusion. The FGF2-FGFR3 axis may promote the progression of esophageal squamous cell carcinoma. The FGF2-FGFR3 axis may be a new direction of targeted therapy for esophageal squamous cell carcinoma. FGF2 and FGFR3 may be used as prognostic markers of esophageal squamous cell carcinoma.